2017
DOI: 10.1063/1.4997610
|View full text |Cite
|
Sign up to set email alerts
|

Study on moving filaments in honeycomb pattern in dielectric barrier discharge

Abstract: We report on the study of moving filaments in a honeycomb pattern in a dielectric barrier discharge system using photomultipliers, a high-speed video camera, and a spectrometer. The honeycomb pattern bifurcates from the hexagonal super-lattice pattern with increasing voltage. It is found that the honeycomb framework is composed of filaments with irregular reciprocating motion, which indicates that the honeycomb framework results from statistical self-organization. The spatiotemporal dynamics show that the patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In addition, the invisible honeycomb lattice is also presented in this work. It is well known that the honeycomb structure, as a basic structure, has been widely reported in the pattern field [16,[18][19][20][21]. However, the invisible honeycomb lattice has not before been presented in a DBD system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the invisible honeycomb lattice is also presented in this work. It is well known that the honeycomb structure, as a basic structure, has been widely reported in the pattern field [16,[18][19][20][21]. However, the invisible honeycomb lattice has not before been presented in a DBD system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the DBD system, known for its incredible accessibility and utility for experimental devices, has been verified as an amazing and preferred system for the investigation of pattern dynamics, because it exhibits an exceptionally great variety and abundance of self-organized patterns [16][17][18][19][20][21][22][23]. Due to the luminous intensity, there not only exist visible discharge filaments to the naked eye or an ordinary camera, which is called normal discharge, but also discharge filaments exist that are invisible to the naked eye or an ordinary camera, which called dark discharge in the DBD system.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cui et al observed a honeycomb pattern with moving filaments, and the central spots were discharged at the centers of the hexagons formed by the moving filaments. [25] Dong's group obtained collective vibration filaments in a hexagonal superlattice pattern, in which the large spots were discharged at the center of the vibrating hexagonal small spots. [26] Prior to this, the effect of the vibrating filaments on the spatiotemporal dynamics of the pattern was the same as that of the static filaments.…”
Section: Introductionmentioning
confidence: 99%